Immune-related adverse events in small-cell lung cancer patients treated with immune checkpoint inhibitors: a comprehensive analysis from the FDA adverse event reporting system - Bai, Yifeng; Wang, Xiaomei; Dai, Xiaoqin; Ma, Qinghua; Hu, Honglin (Frontiers in Pharmacology, 2024)
Background: The discovery and development of immune checkpoint inhibitors (ICIs) have resulted in their application as a novel therapeutic strategy for patients with small-cell lung cancer (SCLC). However, a comprehensive analysis of the potential adverse effects of ICIs in patients with SCLC remains to be conducted. Methods: Adverse event (ADE) reports relating to SCLC patients, submitted to the FDA Adverse Event Reporting System (FAERS) from the first quarter of 2013 to the second quarter of 2022, were extracted for analysis. The extracted data were subsequently screened and analyzed using the reporting odds ratio (ROR) method to assess the AE reports. Results: A total of 4,522 ADE reports were obtained from patients with SCLC who had received either chemotherapy alone or a combination of ICIs with chemotherapy. The ROR analysis identified a total of 91 immune-related adverse events in SCLC patients associated with the ICIs (SCLC-irAEs). Conclusions: This study revealed that the adverse effects resulting from irAEs in SCLC patients predominantly affected the hematologic and gastrointestinal systems, with the most severe cases potentially leading to fatality.